Defective internal allosteric network imparts dysfunctional ATP/substrate-binding cooperativity in oncogenic chimera of protein kinase A - Cristina Olivieri (Nature Portfolio, 2021)
Olivieri, Walker, Karamafrooz et al. show that the fusion of the dynamic J-domain to PKA-C (PKA-CDNAJB1) disrupts the internal allosteric network, attenuating the nucleotide/PKI binding cooperativity. This study suggests that the reduced allosteric cooperativity may contribute to the pathology that PKA-CDNAJB1 drives.